Sports Injuries Prevention, Diagnosis, Treatment and Rehabilitation - Doral, Mahmut Nedim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
In recent years, research studies into sports injuries have provided healthcare professionals with a better understanding of their etiology and natural history. On this basis, novel concepts in the diagnosis and management of these conditions are now being explored. This timely book offers a complete guide to the latest knowledge on the diagnosis and treatment of the full range of possible sports injuries. Individual sections are devoted to biomechanics, injury prevention, and the still emerging treatment role of growth factors, which foster more rapid tissue healing. Sports injuries of each body region are then examined in detail, with special attention to diagnostic issues and the most modern treatment techniques. In addition, pediatric sports injuries, extreme sports injuries, the role of physiotherapy, and future developments are extensively discussed. All who are involved in the care of patients with sports injuries will find this textbook to be an invaluable, comprehensive, and up-to-date reference.
Introduction and History of Sports Traumatology. Prevention of Sports Injuries. Sports Injuries of the Upper Extremity: Shoulder Injuries -- Elbow and Wrist Injuries. Groin Injuries In Sports. Knee Injuries In Sports: A New Perspective on Meniscal Repair and Replacement -- Current Perspectives on Ligament Surgery -- Update on Patellar Injuries. Sports Injuries of Ankle Joint. Current Trends In Cartilage Repair. Stress Fractures. Muscle and Tendon Injuries. Sports and Arthroplasty. Pediatric Sports Injuries. Extreme Sports & Sport Specific Injuries. Role of Physiotherapy in Orthopaedic Sports Medicine. Future of Sports Trauma. Miscellaneous.
Keywords: Medicine; Orthopedics; Sports medicine; Trauma; Medicine & Public Health; Sports Medicine; Orthopedics; Traumatic Surgery